Kapisztránói János és a bártfai Irgalmasság Anyja confraternitás kapcsolata - Dávid Tamás (Acta Universitatis Szegediensis : acta historica, 1996)
The charter written during the stay of Capistran in Poland in 1453 is an important document for the Confraternity of the Mother of Mercy. It was of great relevance for the recently founded (1449) confraternity to be helped and supported by well-known corporations and persons. The charter of Capistran were among the first documents to give grants and indulgence for the confraternity. Then its fame and its influence exerted on the urban life gradually increased and became the number one confraternity of the medieval Hungarian city, Bartfa.